Penerapan Nomor Induk Kependudukan (NIK) sebagai Single Identity Number (SIN) - Rio Widianto (Puslatbang KHAN, 2019)
There are various kinds of identities held by an Indonesian citizen such as: Resident Identity Card (e-KTP), passport, driver's license (SIM), Taxpayer Identification Number (NPWP), etc. These identities make loopholes in disobedience with the rise of fake identity numbers and bad administration. In developed countries that have implemented a single identity number (SIN), a citizen can fulfill all his needs with an efficient, effective and transparent process, and without a complicated bureaucracy. The focus of the discussion in this study is whether Identity Number on e-KTP can be used as a reference, as the basis of information on the application of single identity number (SIN) among all existing identity numbers. Based on the results of the study, there are several problems including the problem of numbering formulations related to the number of digits and numbering codes that accommodate all of the numbering in many identity numbers in various government institutions. To accommodate these problems, technically this study proposes SIN numbering recommendations by covering 3 (three) important points, namely the addition of digits